2016
DOI: 10.1007/s13770-016-9057-6
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenic potential of extracellular matrix of human amniotic membrane

Abstract: Combination between tissue engineering and other fields has brought an innovation in the area of regenerative medicine which ultimate aims are to repair, improve, and produce a good tissue construct. The availability of many types of scaffold, both synthetically and naturally have developed into many outstanding end products that have achieved the general objective in tissue engineering. Interestingly, most of this scaffold emulates extracellular matrix (ECM) characteristics. Therefore, ECM component sparks an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…Amniotic membrane has been reported to provide a niche for the cells to adhere, grow, proliferate, migrate and differentiate, and could possibly contribute to the production of angiogenic micro-environment indirectly which allows AM to improve burn healing [58]. We found that a combination of both AM and AV synergistically improved epithelialization.…”
Section: Discussionmentioning
confidence: 62%
“…Amniotic membrane has been reported to provide a niche for the cells to adhere, grow, proliferate, migrate and differentiate, and could possibly contribute to the production of angiogenic micro-environment indirectly which allows AM to improve burn healing [58]. We found that a combination of both AM and AV synergistically improved epithelialization.…”
Section: Discussionmentioning
confidence: 62%
“…The matrix derived from human amniotic membrane has various components and bioactivities, which allow such matrix to be widely applied in corneal transplantation, retinal regeneration, liver regeneration, and wound healing. [21][22][23][24] Due to its anti-inflammatory effects, anti-fibrotic effect, and angiogenic potentials, [25][26][27][28] we postulate that materials derived from hAM could beneficial for restoring cardiac function following MI.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, the formation of new blood vessels involves multiple processes, such as cell proliferation, migration, adhesion, and tube formation, and CAM suspensions inhibited all these processes in HUVECs, which suggests their anti-angiogenic potential (Yun et al, 2020). In contrast to CAM films, decellularized human amniotic membranes and porcine small intestine submucosa, which showed anti-adhesion properties in peripheral nerve injury, displayed adhesive properties to various cells and expressed an abundant amount of proangiogenic factors, such as vascular endothelial growth factors and fibroblast growth factors (Hashim et al, 2016;Wang et al, 2016). Therefore, every decellularized ECM barrier can physically separate the nerves from the adjacent tissues, but CAM films also have anti-angiogenic and anti-inflammatory properties that cope with the characteristics of anti-adhesive material.…”
Section: Discussionmentioning
confidence: 99%